Digitalisasi Penyelenggaraan Bansos: Studi Tentang Strategi dan Tantangan di Indonesia - Prasetyo, Teguh Dwi; Merini, Dian; Wulandari, Sweetta (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2024)
This study aims to identify the challenges of social assistance implementation in Indonesia, to know whether the digitalization of social assistance can answer these challenges, and to determine the willingness for the digitalization of social assistance. The analysis used in this research is qualitative descriptive analysis, quantitative descriptive and comparative study. The data used in this study are secondary data from the March 2021 SUSENAS and OMSPAN, as well as primary data from surveys on readiness for digitalization of social assistance in five cities with a total of 340 respondents. This research found that the challenges of implementing social assistance programs in Indonesia come from institutions, data, program fragmentation, distribution and utilization of social assistance. The efforts to digitize social assistance can overcome these challenges; however, the willingness towards digitizing social assistance is still constrained by the absence of the pre-condition for the success of digital transformation of social assistance.